IMPLEMENTASI PELAPORAN ESG DALAM AKUNTANSI MANAJEMEN - Husda, Anggun Permata; Alkam, Rahayu (LPPM Universitas Putera Batam, 2025)
This study aims to examine the implementation of Environmental, Social, and Governance (ESG) reporting in management accounting using the Systematic Literature Review (SLR) method. The Watase Uake platform is employed as a supporting tool for collecting, selecting, and analyzing relevant literature. Data were obtained from national and international scientific publications from 2015 to 2025 that discuss the integration of ESG into management accounting practices. The findings reveal that ESG reporting plays a significant role in enhancing transparency, accountability, and strategic decision-making toward sustainability. Management accounting serves a crucial function in providing relevant information for performance measurement and organizational sustainability reporting. However, several challenges remain, including the absence of unified reporting standards, differences in regulatory frameworks, and limited organizational readiness to integrate ESG aspects into internal accounting systems. This study contributes both theoretically and practically to the development of sustainability-oriented management accounting systems and enriches the body of literature concerning the relationship between ESG reporting and management accounting practices.